Toxicity of alpha-ketoglutarate following 14-days repeated oral administration in Wistar rats - Bhattacharya, R.; Gujar, N.; Singh, P.; Rao, P.; Vijayaraghavan, R. (Cellular and Molecular Biology, 2011)
Oral treatment of alpha-ketoglutarate (A-KG) is known to antagonise experimental cyanide poisoning in rodents. Maximum protective efficacy of A-KG has been observed at a dose of 2.0 g kg-1 body weight but no acute toxicity has been observed at this dose level. As a pre-clinical regulatory requirement, sub-acute toxicity of A-KG has to be determined in two different animal species, following repeated exposure by the intended route of use. The present study reports the toxicity and No Observed Adverse Effect Level (NOAEL) of A-KG following 14-days repeated oral administration at low (1.0 g kg-1), middle (2.0 g kg-1) and high (4.0 g kg-1) doses of A-KG in Wistar rats. After termination of the exposure, animals were further observed for 7-days to assess the recovery pattern and residual effects. Clinical signs included diarrhoea at 4.0 g kg-1 in both the sexes and decrease in mean body weight in males. This dose also caused anaemia in females which resolved after withdrawal of treatment. In males, significant increase in absolute and relative weights of organs (adrenal, liver and kidneys) and haematological changes were observed at the end of recovery period, suggesting delayed toxic manifestations at 2.0 and 4.0 g kg-1 dose. However, these observations were not accompanied by any histological changes to suggest any toxicity of A-KG of clinical significance. The NOAEL of A-KG was determined as 1.0 g kg-1 body weight. Although, A-KG is intended to treat acute cyanide poisoning, caution on dosage should be observed during its repeated administration.